MR imaging artifacts produced by dental materials. - Fache, J S; Price, C; Hawbolt, E B; Li, D K (American Journal of Neuroradiology, 1987)
This report evaluates a variety of dental materials with respect to MR imaging artifacts and their mechanisms of production. A 0.15-T superconducting system and an MR phantom were used in assessing imaging artifacts. Several in-vivo studies were also carried out. The dental materials were analyzed for composition and magnetic permeability and the results were compared with the artifacts produced by each material. It was found that the higher the magnetic permeability the greater the artifact produced. Magnetic permeability of a material is generally not predictable on the basis of its composition, however.